Drying and storing apricots in home conditions and measures to combat pest infection - Eshonkulov Najim (International Journal on Orange Technologies, 2021)
In the article, the results and follow-up of the preparation and storage of dried apricots in plastic dishes are presented. The expediency of preparation for storage of dried apricot in plastic dishes by keeping them for 9 days in places where direct sunlight falls has been substantiated. After such preparation and storage, dried apricots are stored for more than 3 years without being damaged by pests. When apricot dried apricots are placed in plastic containers and stored in direct sunlight for 9 days, the plastic does not kill the worms due to the increased pressure inside the plastic container and high temperatures, killing insect eggs, fungi and bacteria.